Pengaruh Komposisi Media Tanam Terhadap Pertumbuhan Tanaman Kemangi (Ocimun Basilicum L) Secara Vertikultur - I Gede Krisna Wardana; Ni Luh Kartini; Ni Nengah Soniari (Fakultas Pertanian, Universitas Udayana, 2020)
The research objective was to determine the effect of the composition of the growingmedium on the growth of basil plants. This research was carried out in Banjar DinasBelumbang Kelod, Belumbang Village, Kerambitan District, Tabanan Regency, inJanuary-March 2020. Used was a simple randomized block design (RAK). Thecomposition of the planting medium consisted of vermicompost fertilizer, soil and sandweighing 5 kg per treatment. The treatments tested were as follows M0: Soil + Sand(100%); M1: Soil + vermicompost fertilizer + sand (50%: 50%: 0%); M2: Soil +Kascing Fertilizer + Sand (50%: 0%: 50%); M3: Soil + vermicompost fertilizer + sand(50%: 30%: 20%); M4: Soil + Kascing Fertilizer + Sand (50%: 20%: 30%); M5: Soil +vermicompost fertilizer + sand (40%: 40%: 20%); M6: Soil + Kascing Fertilizer + Sand(40%: 30%: 30%); M7: Soil + Kascing Fertilizer + Sand (30%: 40%: 30%); M8: Soil +vermicompost fertilizer + sand (30%: 50%: 20%). The results showed that the effect ofmedia composition gave significantly different results on plant height, fresh weight onsoil, total fresh weight, dry weight above soil, total dry weight, C-organic content andmicroorganism population. The treatment of soil composition + vermicompost fertilizer+ sand (50%: 20%: 30%) gave the best results for the growth of basil and the totalpopulation of soil microorganisms. The highest yield of fresh basil plant wet weight was40.10 grams, an increase of 2.3% compared to the control. Then the microorganismpopulation increased by 50% compared to the control.